A proposal to build a reading center in Barangay Diit, Tacloban City Leyte (Region VIII) - Vergara, Lucille D.; Yang, Jackson V. (Quezon City Institute of Library and Information Science, University of the Philippines Diliman, 2002)
The reading center is going to be established for the residents of Brgy. Diit, Tacloban City.The reading center will be located at the Brgy. Hall. Its collections will focus on agriculture, family health, home economics, young adult's literature and children's literature. It will offer services such as lending reading materials, story-telling for children and a movie-viewing program for the adults in the community.
The reading center will be a priority project of the Sangguniang Kabataan in Brgy. Diit in the year 2003. The organization aims to collect an amount of ten thousand pesos from generous individuals and various organizations in Tacloban City. Letters asking for donations will be sent to the offices of the local politicians and local establishments. The donations will be used for the needed concrete materials such as shelves, tables, chairs and books. The main office of the Department of Agriculture Quezon City has given free reading materials on agriculture. The titles for children's literature, young adults and home economics have only been cited but not yet acquired. The members of the Sangguniang Kabataan volunteer for the supervision of the reading center. The reading center will be open from 8 A.M. to 12 P.M.The reading center's establishment will be depended on the organization behind it which in the Sangguniang Kabataan of Brgy. Diit.
Vita.
Thesis (Bachelor of Library and Information Science)
Keywords: Reading rooms -- Philippines -- Tacloban City